Branching Patterns and Variations of Facial Artery and Clinical Importance: A Cadaveric Study - Cagatay Barut; Eren Ogut; Zeynep Askin; Hasan Alicikus (Dubai Medical Journal)
Introduction: The facial artery (FA) was observed with distinctive variations and anomalous, which occur during the embryological developmental process due to the ablation of neural crest cells that impact embryonic aortic arch vessels, resulting in distinctive branching patterns. Therefore, this study aimed to investigate the types, clinical importance, localization, and differences of FA in fixed cadavers according to gender and body side. Methods: The current study was conducted on 19 formalin-fixed cadavers (68.4% males, n = 13; 31.6% females, n = 6). The types, variations, prevalence, and distance to nearby surgical landmarks of FA were recorded on both sides. Measurements were taken with a surgical microscope (Zeiss Meditec, Berlin, Germany) and a digital caliper (INCA, DCLA-0605, 0.6–150 mm). Results: Angular type % 73.1 (n = 14, right; n = 19, left), labial type % 5.3 (n = 1, right), alar type % 5.3 (n = 1, right), and nasal type % 5.3 (n = 1, right) were detected. The following parameters were significant according to gender; the distance between the ala of the nose and the origin of the FA on both sides (p = 0.007 right; p = 0.018 left), the diameter of FA at the cheilion (p = 0.019 left), diameters of the superior and inferior labial arteries at their origin (p = 0.031 right; p = 0.025 right) and PO lines. Conclusion: The significant differences in gender according to the distance of the FA and its branches from the origin should be considered to reduce complications during surgery. The differences in studies according to the types and variations of FA may be due to the scale of the study, gender, or study design.